Effect of dietary supplementation of sodium salt of isobutyric acid on rumen fermentation and nutrient utilization in crossbred cattle fed wheat straw based low protein and urea containing diets - MISHRA, A K; THAKUR, S S (The Indian Journal of Animal Sciences, 2014)
The present experiment was conducted to observe the effect of dietary supplementation of sodium salt of isobutyric acid in low protein and urea containing wheat straw based diets on ruminal fermentation and nutrient utilization in crossbred cattle. Twelve crossbred rumen fistulated cattle, divided into 3 similar groups, were fed a basal diet consisting of wheat straw; concentrate mixture and green maize fodder in 40:40:20 proportion (G1), Basal diet+ isobutyric acid (SCFA) @0.75 % of basal diet (G2) and basal diet +SCFA+ urea to replace 1/3rd of dietary nitrogen (G3). The feed intake among different experimental groups did not differ significantly and the average total DMI (kg/100 kg B.W.) was 2.01.2.28 and 2.24 kg/d. in 01, 02 and 03 , respectively. The dietary supplementation of isobutyrate improved the DM, OM, NDF and cellulose digestibility coefficients by 14.46, 10.51, 10.70 and 11.31 %, respectively, in SCFA and BCFA + urea fed groups over that fed diet without BCFA (01). The total N retention on BCFA supplementation was improved mainly due to decreased urinary N excretion. The concentrations of rumina 1 total N (mg/100 ml SRL) were 37.07, 34.77 and 34.64 in 01, 02 and 03, respectively. Dietary supplementation of Na-salt of isobutyric acid significantly (P<0.01) reduced the ruminal ammonia N concentration as compared to land the mean values (mg/100 ml) were 13.18, 9.42 and 11.15 in G1. 02 and 03. The TCA-N concentration (expressed as % of N intake) was higher (P<0.01) in BCFA fed groups. Similarly, ruminal TVFA concentrations were higher (P<0.01) in BCFA supplemented groups (101.14 and 95.62 mM/litre) than without BCFA (93.05 mM/litre). Among VFAs, the concentration of acetate was higher (P<0.01) in BCFA supplemented groups (71.07 and 69.73 mM/litre) as compared to 01 (64.98 mM/litre). However, the concentration of propionate and butyrate remained unchanged. The dietary supplementation of Na-salt of isobutyric acid in low protein and urea supplemented diets improved the nutrient utilization and rumen fermentation characteristics.